Comparative assessment of solvents toxicity using early life stages of amphibians and cell lines: a case study with dimethyl sulfoxide - Coelho, Sónia Dias; Campos, Diana; Almeida, Mónica; Quintaneiro, Carla; Oliveira, Miguel; Lopes, Isabel (Frontiers in Toxicology, 2026)
The reduction in the number of animals being used in experimental assays has been a concern of the scientific community. In this sense, non-animal alternative methods have been increasingly tested. This study intended to explore how cell-based responses compare to organismal outcomes and if the former models could contribute to minimizing the number of live animals needed in subsequent stages of hazard/risk assessment of chemicals on amphibians. For this, the toxicity of the commonly used solvent dimethyl sulfoxide (DMSO) was assessed in early life stages (embryos and tadpoles) of two anuran species (Xenopus laevis and Pelophylax perezi) and in 2 cell lines of X. laevis (A6 and XTC-2). In the in vivo assays, mortality, teratogenic effects, and biometric parameters were evaluated, while for in vitro assays, the assessed endpoint was viability. Overall, the obtained data suggest similar sensitivity of both species and life stages to DMSO. The 96 h-LC50 estimated for embryos and tadpoles were, respectively, 2.19% and 2.56% for X. laevis and 3.19 and 3.41 for P. perezi. The solvent DMSO induced several malformations in early life stages, which may have implications for the fitness of organisms at later stages. A slightly higher sensitivity to DMSO was observed in the in vivo approaches comparatively to in vitro approach (72 h-LC50 of 3.10% and 2.62% for A6 and XTC-2, respectively), though it can not be considered significantly different. As such, it is suggested that the latter approach may be considered to serve for first screenings of the ecotoxicity of organic solvents. Such a strategy of using in vitro assays as screening tools, has the potential to reduce the number of animals to be used in subsequent in vivo testing phases by providing information for the refinement of concentrations to be tested in in vivo assays, thereby supporting both reduction and replacement objectives.